Antioxidant, Antimicrobial Activity and Toxicity Test of Pileamicrophylla - Chahardehi, Amir Modarresi; Ibrahim, Darah; Sulaiman, Shaida Fariza (Hindawi Publishing Corporation, 2010)
A total of 9 plant extracts were tested, using two different kinds of extracting methods to evaluate the antioxidant and antimicrobial activities fromPileamicrophylla (Urticaceae family) and including toxicity test. Antioxidant activity were tested by using DPPHfree radical scavenging, also total phenolic contents and total flavonoid contents were determined. Toxicity assay carried out by using brine shrimps.Methanol extract of method I (ME I) showed the highest antioxidant activity at 69.51±1.03. Chloroform extract of method I (CE I) showed the highest total phenolic contents at 72.10±0.71 and chloroformextract of method II (CE II) showed the highest total flavonoid contents at 60.14 ± 0.33. The antimicrobial activity of Pilea microphylla extract was tested in vitro by using disc diffusion method and minimum inhibitory concentration (MIC). The Pilea microphylla extract showed antibacterial activity against some Gramnegative and positive bacteria. The extracts did not exhibit antifungal and antiyeast activity. The hexane extract of method I (HE I) was not toxic against brine shrimp (LC50 value was 3880 μg/ml). Therefore, the extracts could be suitable as antimicrobial and antioxidative agents in food industry.